KEBIJAKAN ARAB SAUDI DALAM KONFLIK YAMAN PADA MASA PEMERINTAHAN RAJA SALMAN - Waritsa Yolanda; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research aims to explain Saudi Arabia’s Foreign Policy towards Yemen’s Conflict under King Salman’s Era. The research uses the Perspective of Neorealism which believes that international system is anarchy, cooperation build up to maximize the power of the country to survive in the anarchy situation. Theory of decision making process that used in this research notice to explain Saudi Arabia’s decision making process to get involve in Yemen’s conflict. This research is also supported by the concept of intervention which notice to explain the type of intervention that Saudi Arabia used when doing the intervention on Yemen’s conflict under King Salman’s era.The method used in this research from the measurement of the data is qualitative research method, and from the way of processing data is explanative method. Furthermore, the technique of data analysis is based on data from literature studies with the consideration that the data is capable in providing information regarding the problem under research.The results of the research explains that the reason Saudi Arabia intervened by doing Operation Decisive Storm, Operation Restoring Hope and Operation Golden Victory in the Yemen conflict was because Saudi Arabia wanted to prevent the expansion of Yemen’s conflict. Keyword : Military Intervention, Regional Leader, Foreign Politcy, King Salman, Operation Decisive Storm, Operation Restoring Hope, Operation Golden Victory